Sosialisasi KTR “Siswa Cerdas Tanpa Rokok” di SMK Syuhada Banjarmasin - Yeni Riza; Meilya Farika Indah; Eddy Rahman; Husnul Khatimatun Inayah (Al-Khidmah, 2019)
The results of riskesdas years 2013 mentioned the prevalence of smokers in indonesia reach 36,5 % consisting of 68,8 % smokers laki-laki and 6,9 %. women smokersThis fact made indonesia ranked third in the event of an epidemic in the world. highest cigarette consumption. The increasing prevalence of smoking and reach the burden of disease and economic as well as a result of the decline in cigarette consumption of health care and quality of human resources ( human resources ) indonesia in the days to come ( febriani, 2014 ). Therefore will be held this community activity devotion to the students in order to prevent kids from smoking, especially at the age of who is a minor.Objectives of the activities is to come up with the knowledge for the for the youth pt pgn promised to supply student of class two of vocational high school on the prohibition area of without the city from cigarette smoke and the dangers of smoking for the health of as well as intelligence to make the young generation which is free from cigarettes . The main target or targeted from the activities of these are the students or a student of two smk witness banjarmasin who beramatkan in the way of a brig .Jend .Hasan basri no. 23 banjarmasin north, city banjarmasin Methods used in this activity is through the video, lectures, and discussion and integration.Through socialization activities in students in smk area - to the participants without cigarette understand the whole material extension that have characterized by participants disampai fully answers the questions given instructor and team after the socialization to students in smk - about “KTR and the danger of cigarette” is  61 students (81 %) having attitude to quit smoking and the remaining 14 students ( 19 % ) still no desire to quit smoking.Key Words: KTR, danger, smoking, students